Evaluation of characteristic-to-total spectrum ratio: Comparison between experimental and a semi-empirical model. (June 2015) - Lopez Gonzales, A.H.; Tomal, A.; Costa, P.R.
Abstract: Primary X-ray spectra were measured in the range of 80–150 kV in order to validate a computer program based on a semiempirical model. The ratio between the characteristic and total air Kerma was considered to compare computed results and experimental data. Results show that the experimental spectra have higher first HVL and mean energy than the calculated ones. The ratios between the characteristic and total air Kerma for calculated spectra are in good agreement with experimental results for all filtrations used. Highlights: Primary X-ray spectra were measured in the range of 80–150 kV. Primary X-ray spectra were computed using the TBCmod code, from 80 to 150 kV. Characteristic to total spectrum ratio was used to validate the TBCmod code. X-ray spectra computed with TBCmod are in good agreement with experimental results.